Implementasi Pembelajaran Mitigasi Bencana Kebakaran di Taman Kanak-Kanak Dharma Wanita Sendanghaji Tuban - Sa’adah, Dwi Aminatus; Amatul, Aisyah; Siti Mawatdatul Mukholisoh; Siti Juriyah (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2025)
Fire is a disaster that can occur suddenly, requiring early mitigation efforts to reduce risks and impacts. This study aims to enhance the understanding of Dharma Wanita Kindergarten students in Sendanghaji Merakurak Tuban regarding fire disaster mitigation through education, simulation, and introduction to fire extinguishers. The activity was conducted in February 2025 by PPL students of IAINU Tuban using socialization methods, evacuation simulations, and demonstrations of portable fire extinguishers. The evaluation results through pretests and posttests showed a significant increase in students' understanding: from 63% to 92% regarding fire disasters, from 34% to 93% in understanding the evacuation process, and from 35% to 87% in recognizing fire extinguishers. The findings confirm that a practice-based and interactive educational approach effectively improves students' preparedness for fire disasters. Therefore, continuing mitigation programs by involving various stakeholders, including schools, universities, and relevant agencies, is essential to expand educational coverage and enhance children's preparedness from an early age.